Digital Literacy Mentoring and Training Through Online Marketing for MSMEs - Widiati, Ari; Saragih, Eka Junila (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2025)
This community service program aims to improve digital literacy of MSMEs through mentoring and online marketing training. The Community-Based Research (CBR) approach is applied by involving students as facilitators to support knowledge transfer and implementation of digital literacy at the community level. The training includes the use of social media, e-commerce, and fintech as marketing tools. The results of the activity show that 70% of MSMEs have started to utilize digital platforms for promotion, with an increase in interaction on social media up to five times. However, there are challenges faced by MSMEs in implementing digital literacy including limited infrastructure, access to technology, and low understanding of data-based marketing strategies. Some MSMEs also experience obstacles in maintaining consistent promotions and adapting to technological changes. Therefore, ongoing assistance and synergy between academics, business actors, and the government are needed to ensure sustainable impact. This program proves that effective digital literacy can increase the capacity of MSMEs and students in the digital ecosystem, as well as encourage technology-based economic growth.